NO ORDINARY HEARSAY! A Discussion of Minister of Police v RM M, Safety and Security Sectoral Bargaining Council and M Smith NO (2017) 38 ILJ 402 (LC) - Nicola Whitear (Obiter, 2018)
One is constantly reminded not to emulate the criminal courts when conducting disciplinary enquiries, nor, for that matter, labour dispute resolution arbitrations.The locus classicus dealing with the appropriate manner to conduct disciplinary enquiries is the Avril Elizabeth Home for the Mentally Handicapped v CCMA ([2006] 9 BLLR 833 (LC)) case. It was in this case, which has been quoted and followed innumerable times (a significant recent case being that of BEMAWU v SABC [2016] ZALCJHB 74 (2 March 2016)), that the court emphasised item 4(1) of the Code of Good Practice: Dismissal (Schedule 8, Labour Relations Act 66 of 1995) which provides that there does not have to be a formal disciplinary enquiry. The court indicated that the approach outlined in the code was a “significant and fundamental” departure from the criminal justice model, which “likened a workplace disciplinary enquiry to a criminal trial”.It is also, however well-established that arbitrators, and disciplinary chairpersons, must follow basic rules of fair procedure and evidence.This tension between avoiding over-formality while remaining true to basic rules of evidence and procedure is again evident in a recent case (Minister of Police v RM M Safety and Security Sectoral Bargaining Council (2017) 38 ILJ 402 (LC)), which deals with the proper manner to treat hearsay evidence in a labour dispute resolution arbitration.The case sends the message that if the proceedings of a disciplinary enquiry are conducted with a relatively high degree of formality, and fairly scrupulous adherence to what might be described as the criminal justice model – then one might be able to create a prima facie case against the dismissed employee at the de novo arbitration hearing while avoiding the re-calling of the witnesses – and instead by simply tendering the (hearsay) record of the disciplinary proceedings. The case also contributes to the jurisprudence seeking to protect  (such as children, in casu) by canvassing means by which such witnesses may be spared having to repeatedly testify to traumatic events.